Curium(iii) radiation-induced reaction kinetics in aqueous media. Issue 31 (23rd July 2021) - Horne, Gregory P.; Grimes, Travis S.; Zalupski, Peter R.; Meeker, David S.; Albrecht-Schönzart, Thomas E.; Cook, Andrew R.; Mezyk, Stephen P.
Abstract : Pulsed electron reaction kinetic data for Cm(iii ) suggest that radiation-induced Cm(ii ) and Cm(iv ) transients could exist in aqueous solutions and be available to undergo subsequent redox chemistry. Abstract : Insight into the effects of radiolytic processes on the actinides is critical for advancing our understanding of their solution chemistry because the behaviour of these elements cannot be easily separated from the influence of their inherent radiation field. However, minimal information exists on the radiation-induced redox behaviour of curium (Cm), a key trivalent transuranic element present in used nuclear fuel and frequently used as an alpha radiation source. Here we present a kinetic study on the aqueous redox reactions of Cm(iii ) with radicals generated through the radiolysis of aqueous media. In particular, we probe reaction kinetics in nitric acid solutions that are used as the aqueous phase component of used nuclear fuel reprocessing solvent systems. Second-order rate coefficients ( k ) were measured for the reaction of Cm(iii ) with the hydrated electron (eaq −, k = (1.25 ± 0.03) × 10 10 M −1 s −1 ), hydrogen atom (H˙, k = (5.16 ± 0.37) × 10 8 M −1 s −1 ), hydroxyl radical (˙OH, k = (1.69 ± 0.24) × 10 9 M −1 s −1 ), and nitrate radical (NO3 ˙, k = (4.83 ± 0.09) × 10 7 M −1 s −1 ). Furthermore, the first-ever Cm(ii ) absorption spectrum (300–700 nm) is also reported. These kinetic data dispel the status quo notion of Cm(iii ) possessing little to no redox chemistry in aqueous solution, and suggest that the resulting Cm(ii ) and Cm(iv ) transients could exist in irradiated aqueous solutions and be available to undergo subsequent redox chemistry with other solutes.